Management of patients with idiopathic pulmonary fibrosis in clinical practice: the INSIGHTS-IPF registry - Behr, Jürgen; Kreuter, Michael; Herth, Felix (The European respiratory journal, 2015)
After introduction of the new international guidelines on idiopathic pulmonary fibrosis (IPF) in 2011, we investigated clinical management practices for patients with IPF according to physicians' diagnoses., A prospective, multicenter, noninterventional study with comprehensive quality measures including on-site source data verification was performed in Germany., 502 consecutive patients (171 newly diagnosed, 331 prevalent; mean±sd age 68.7±9.4 years, 77.9% males) with a mean disease duration of 2.3±3.5 years were enrolled. IPF diagnosis was based on clinical assessments and high-resolution computed tomography (HRCT) in 90.2%, and on surgical lung biopsy combined with histology in 34.1% (lavage in 61.8%). The median 6-min walk distance was 320 m (mean 268±200 m). The mean forced vital capacity was 72±20% pred and diffusing capacity of the lung for carbon monoxide was 35±15% pred. No drugs were administered in 17.9%, oral steroids in 23.7%, N-acetylcysteine in 33.7%, pirfenidone in 44.2% and other drugs in 4.6% of patients. Only 2.8% of the cohort was listed for lung transplantation., IPF patients were diagnosed in line with the new guidelines. They had more severe disease than those enrolled in recent randomised controlled trials. In addition to HRCT, the frequency of lung biopsies was surprisingly high. Treatment patterns varied substantially., This largest published registry of IPF patients shows surprising disease severity and treatment variation http://ow.ly/JbWRn